ESTIMASI KANDUNGAN FOSFOR PADA TANAMAN NANAS MENGGUNAKAN UNMANNED AERIAL VEHICLE (UAV) DI PT. GREAT GIANT PINEAPPLE, LAMPUNG - Revaldy Andika; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
PT. Great Giant Pineapple (PT. GGP) is the largest pineapple plantation company in Indonesia, with a land area of approximately Â±33,000 ha and dominated by soil types in the form of Ultisols. Soil fertility at PT. GGP tends to have relatively low nutrient content, one of which is phosphorus due to Al fixation. The nutrient P in pineapple is used to stimulate root growth, accelerate the ripening of fruit and seeds. Symptoms arising from P deficiency will experience stunted growth (stunted), and the pineapple will become imperfect. This study aimed to estimate the P nutrient content in pineapple plants using vegetation indexes in the form of GNDVI (Green Normalized Difference Vegetation Index). The study was carried out by taking aerial photographs and samples of pineapple plants in the 1 months phase before forcing and 1 months after forcing (F-1 and F+1), laboratory analysis, statistical analysis, and making distribution maps. The results showed that the vegetation index could estimate the nutrient content of P using the best estimation model. This was evidenced from the results of the correlation test which shows a very strong and real relationship of 0.81-0.82 with the regression test results of 66%-67%. In addition, the results of the validation test using the paired t-test showed that the t-count was smaller than the t-table of 2.30, which means that the estimated GNDVI vegetation index and the P nutrient content of pineapple plants showed no significant difference.